2023
DOI: 10.3390/biology12101288
|View full text |Cite
|
Sign up to set email alerts
|

Tunneling Nanotube: An Enticing Cell–Cell Communication in the Nervous System

Sunayana Dagar,
Srinivasa Subramaniam

Abstract: The field of neuroscience is rapidly progressing, continuously uncovering new insights and discoveries. Among the areas that have shown immense potential in research, tunneling nanotubes (TNTs) have emerged as a promising subject of study. These minute structures act as conduits for the transfer of cellular materials between cells, representing a mechanism of communication that holds great significance. In particular, the interplay facilitated by TNTs among various cell types within the brain, including neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 109 publications
0
1
0
Order By: Relevance
“…Although the mechanistic process that leads to this NVU-behaviour relationship deserves to be studied in depth, our results suggest the existence of close communications between NVU cells at the local level and/or between distinct brain areas. It has been recently demonstrated that brain cells, including microglia, astrocytes and endothelial cells can communicate each other by forming tunnelling nanotubes (for review see (35)). To our knowledge, however, no interregional relationships have been identified between components of the NVU.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanistic process that leads to this NVU-behaviour relationship deserves to be studied in depth, our results suggest the existence of close communications between NVU cells at the local level and/or between distinct brain areas. It has been recently demonstrated that brain cells, including microglia, astrocytes and endothelial cells can communicate each other by forming tunnelling nanotubes (for review see (35)). To our knowledge, however, no interregional relationships have been identified between components of the NVU.…”
Section: Discussionmentioning
confidence: 99%